Pengaruh Kepatuhan Pasien Dan Ketepatan Terapi Terhadap Hasil Terapi Pasien Penyakit Paru Obstruksi Kronik di Poli Paru RSUD Dr. Moewardi Surakarta - , ANITA MURSIANY; , Prof. Dr. Zullies Ikawati, P.hd., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Patient adherence to treatment of chronic obstructive pulmonary disease is important for optimizing the disease management. A low level of adherence may lead to increasing morbidity, medical expense, hospitalization, and mortality. Medication accuracy becomes one of the important factors in determining the success of a therapy. The research aimed to identify the influence of patient adherence and therapy accuracy on the outcome of therapy for patients with chronic obstructive pulmonary disease in the pulmonary clinic of Dr. Moewardi Hospital Surakarta in order to increase the therapy effectiveness and patientsâ quality of life. The research was a descriptive, analytic, observational research with a cross- sectional research plan. The data gathering was conducted prospectively using the purposive-sampling method for the patients with chronic obstructive pulmonary disease in the pulmonary clinic of Dr. Moewardi Hospital Surakarta. The data were obtained from questionnaires, medical records, and interviews with the patients. The questionnaire used the Modified Morisky Scale to determine the level of patient adherence and the COPD Assessment Test to identify the outcome of therapy for patients with chronic obstructive pulmonary disease. The number of samples that fulfill the inclusive and exclusive criteria was 48 patients. The result showed that 37.5% of the patients with chronic obstructive pulmonary disease in the pulmonary clinic of Dr. Moewardi Hospital Surakarta had a high level of adherence, 41.6% of them were partially adherent, and 20.83% of them had a low level of adherence. The correlation between patient adherence and therapy outcome was shown by the chi-square analysis result of r = 0.174. The correlation was not significant because the clinical condition of the patients with chronic obstructive pulmonary disease had been stable. The accuracy of therapy occurred in 25 cases (52%). Inaccuracy of treatment happened in 23 cases: 12 cases due to indication, 9 cases because of drug selection, 1 case because of dosage, and 1 case due to appropriate patient. The correlation between treatment accuracy and therapy outcome was indicated by the chi-square analysis result of r = 0.773. This correlation was positive, so it meant that the higher the treatment accuracy was, the better the therapy outcome was.